A simple and universal electrochemical assay for rapid field monitoring of E120 food additive - Muriqi, Sali; Patočka, Jan; Červenka, Libor; Sýs, Milan (Academic Press (Elsevier), 2024)
A cost-effective electrochemical method was developed to rapidly monitor carminic acid (E120 food additive) levels. This assay simplifies the process by directly applying 50 mu L of liquid sample onto a commercially available screen-printed voltammetric sensor. The subsequent anodic oxidation specifically targets the carminic acid within the complex matrix. To achieve maximum selectivity with regard to the variable composition of common beverages, the peak area current response was calibrated within a linear range 0.01-50 mg per 100 mL(-1) of carminic acid, with a sensitivity of 2.232 mu A V mg(-1) mL, and a detection limit of 4 x 10(-3) mg per 100 mL. A satisfactory precision (relative standard deviation less than 4.5 %) has been found with a single use of five sensors. Practical applicability of the developed screening electrochemical assay in the food safety control was successfully verified in analysis of sweet candies, soft beverages, and energy drinks.
Jednoduchý a univerzální elektrochemický test pro rychlé terénní monitorování E120 potravinářského aditiva
Keywords: Carminic acid; Disposable sensors; Electrochemical assay; Food colourant; Screening analysis; Kyselina karmínová; Jednorázové senzory; Elektrochemický test; Potravinářské barvivo; Screeningová analýza